The Incidence of Lipoprotein Disorder in Patients with Psoriasis Attending in a Tertiary Care Hospital of Bangladesh (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: psoriasis; dyslipidemia; diabetes; hypertension